HUBUNGAN ANTARA MOTIVASI DAN KEDISIPLINAN SISWA DENGAN HASIL BELAJAR IPA SISWA KELAS VII SMP SE-KECAMATAN PANDAK - Akfi Fadlin Nur Fuadi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This study aim was to determine the correlation between motivation and discipline of students on science result study of 7th-grade student secondary school of subdistrict Pandak in academic year 2014/2015. The study population included all students of the 7th-grade secondary school of subdistrict Pandak with totally 110 students. Descriptive research results showed that the students' motivation and discipline of the students were in the very high category and Science learning outcomes at the high category. Finally, the results of correlation analysis showed that the correlation and coefficient of 0.623, included the strong category, which meant that there was a positive relationship between motivation and discipline of students with learning outcomes IPA junior class VII Pandak throughout the school year 2014/2015.